Cognitive bases of toponym appellatives of Kyzylorda region - Abasilov , А.М.; Tuyakbayev, Ғ.Ә.; Saryshova, К.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
At the present stage in the new anthropocentric paradigm, the consideration of onomastics, including toponymy, in the cognitive aspect, contributes to the acquisition of new datain connection with the study of linguistics. The samples of the world, formed in the knowledge of a certain nation, form the onomastic space of all proper names. It is known that the nature and structure of proper names are influenced by various extra-linguistic factors as geographic, social, historical, and cultural. Proper names can be created both on the basis of traditionally formed “ready-made” words of the language, and as a result of the linguistic creativity of individuals. Consequently, among proper names, along with the original names, names that have arisen on the basis of various connotational derivations are also distinguished. In the article, based on the toponyms of the Kyzylorda region, various approaches to understanding the essence of appellatives, which were formed on the basis of proper names and represent an onomastic linguistic unit containing cognitive-historical information, are considered. There are different cognitive mechanisms that determine the formation of speech and linguistic meanings of these lexical units. The structure of the matrix format of knowledge contained in the appellative is analyzed in detail, as well as the concept expressed through the appellative-toponym and explained in relation to the cognitive context of the matrix. In addition, the authors pay special attention to the fact that the identification of the linguistic essence of appellatives-toponyms is one of the urgent problems and, at the same time, a promising area of linguistic and philological research in the future.